Public servant perception towards Person with Disabilities (PWDs) in Pejabat Tanah Dan Galian Selangor (PTGS) at the Selangor State Secretary's Office / Muhammad Nadzirul Hafizie M Daud - M Daud, Muhammad Nadzirul Hafizie (2019)
The involvement of Person with Disability (PWDs) in employment sector has brought to several different perspectives on how this group being treated by the employers and society at large. Thus, the issue of discrimination toward this group is not a new issue, and hence, as an employer, the issue should be triggered to ensure the harmony working environment of its employees. The research examines the public servants 'I perception towards Person with Disability (PWDs) in Pejabat Tanah Dan Galian Selangor (PTGS) at The Selangor State Secretary's Office. A census has been conducted by having response from 184 respondents and it will examine the factors that contribute to public servant perception, which is knowledge, attitude and awareness. The perception of public servants in the department is highly lead by their attitude towards PWDs. The employees appear to be still unaware the PWDs in their working environment and perceived a negative perception towards them. Yet, the study is focusing on a small scope, and does not explain the situation of whole population of PWDs in employment sector in Malaysia.